The Diffusion of Health Innovations from Developing to Developed Countries - Dadwal, Viva (Université d'Ottawa | University of Ottawa, 2012)
Influencing the pace at which health innovations spread through geographic regions is a budding field of research of interest to health care professionals, development-aid agencies, private sector entrepreneurs, non-governmental organizations, and public institutions alike. There is however little diffusion research in the field of health that examines the importance of innovation characteristics in the innovation adoption process. There is also a gap in research literature when it comes to assessing the likelihood of diffusion of health innovations from developing to developed countries. As a result, our understanding of innovation diffusion processes between countries is fragile, and the existing theoretical literature on this phenomenon limited. This paper is a first attempt at evaluating the conditions under which health care innovations from developing countries may or may not diffuse to developed country settings. As such, the paper is designed to articulate a conceptual model for evaluating the diffusion of health care innovations from developing to developed countries. The paper reviews prior research on the diffusion of innovations and focuses on the role of innovation characteristics in bringing about innovation adoption. In particular, Everett Rogers’s work on the perception of innovation attributes aids in the development of a general model for studying the diffusion of innovations. The exploratory framework presented in this paper is also predicated on the need to distinguish between policy, programme, and practice-based health innovations. Three examples are then used to briefly illustrate why health policy-related innovations are less likely to diffuse than health programme-based innovations and why health programme-based innovations are less likely to diffuse than health practice-based innovations. The conceptual model and brief illustrations provide new insights into the underlying mechanisms driving the diffusion of health innovations and bridges the shortfalls of prior work assumed in this area. These classifications shape the way decision-makers and the public evaluate and process innovation information when responding to new health innovations. In particular, the paper suggests that if the concept of innovation diffusion between countries can be clarified further, then it may become easier for policymakers and practitioners to evaluate, adopt and procure innovations in ways that can realistically recognize, encourage and give priority to truly valuable innovations.